Is pentraxin-3 stronger than C-reactive protein to determine inflammation in peritoneal dialysis patients? - Gursu, MELTEM; GÜRSU, MELTEM; OZTURK, S.; AYDIN, Z.; KARADAG, S.; DOVENTAS, Y.; KOLDAS, M.; UZUN, S.; SUMNU, A.; KAZANCIOĞLU, RÜMEYZA; KAZANCIOĞLU, RÜMEYZA (My University, 2012)
Pentraxin-3 (PTX-3) is the prototype of long pentraxins and is produced by many tissues and organs including vascular endothelial cells in response to pro-inflammatory signals. It is thought to be an independent indicator of disease activity. We analyzed the correlation of PTX-3 with other markers of inflammation in peritoneal dialysis (PD) patients. Non-diabetic patients on chronic PD program who meet the dialysis adequacy criteria and who had no active infectious/inflammatory disease were included. Demographic and clinical parameters were recorded as well as hsCRP, fibrinogen, interleukin-6 (IL-6) and PTX-3 levels; and the correlation between them were studied. Twenty-five patients (mean age: 45.7 +/- 12.5 years; female/male ratio: 16/9) were included. Mean PTX-3 level was 2.16 +/- 2.76ng/ml. PTX-3 was found to be correlated positively with only IL-6 among inflammatory markers (r=0.827; p<0.001) but not with hsCRP. With linear regression model, IL-6 was the only independent determinant of PTX-3 levels. PTX-3 may be a more valuable marker of inflammation than CRP in patients on PD.
Keywords: dialysis